Effects of woody debris on alluvial sediment differentiation and particulate organic matter accumulation in a mountainous forest stream in the Polish Carpathians - Słowik-Opoka, Ewa; Michno, Anna; Jarosz, Agnieszka (Frontiers in Forests and Global Change, 2024)
Woody debris (WD) stabilizes riverbeds, creates habitats, supports biodiversity, and enhances water quality in ecosystems. This study investigates the impact of WD on sediment characteristics and particulate organic matter (POM) accumulation in the Roztoka stream, located within a forested catchment in the Polish Carpathians. The focus is on the influence of different WD types: coarse (CWD, length >1m and diameter >10cm), fine (FWD, length <1m and diameter <10cm), and mixed (MWD, a combination of CWD and FWD) on sediment differentiation and POM accumulation. Stand age, ranging from 20 to over 120 years (in 20-year intervals), was also analyzed as a factor affecting WD structure and POM deposition. Results indicate that MWD had the greatest effect on sediment differentiation, with mean grain size (Mz) ranging from -3.91 phi to -0.95 phi. Stand age significantly influenced POM accumulation, with the highest content (19.51%) observed in age classes III and VI. Older stands (>120 years) had a diminished effect on both WD structure and POM accumulation. This study underscores the critical role of WD in sediment differentiation and provides insights for improving the ecological function of natural streams. Although the findings are region-specific, they have broader implications for similar temperate mountainous forests.